Different methods for textural evaluation of freeze-dried candies during storage - Archaina, Diego Alberto (2023)
The textural changes during storage of two freeze-dried candies developed from blackcurrant fruits, unflavored yogurt, and different alternative sweeteners, one sweetened with honey/isomalt (HI) and another sweetened with isomalt/stevia (IS), were analyzed using three different methods (instrumental, sensory, and image analysis). Fresh candies were in the supercooled state and presented different structural and textural characteristics (HI: compact and homogeneous, and IS: porous and crunchy), with Fmax values of 139 ± 14 and 174 ± 16 N for HI and IS, respectively. After storage, the instrumental analysis showed approximately 60% average drop in Fmax and W values, in agreement with the decrease observed by sensory analysis in hardness, fracturability, and crispness. Image analysis showed an increase in parameters related to the homogeneity and the uniformity/smoothness for HI. Pearson's correlation coefficients analysis showed that there was a good correlation between the three techniques used, suggesting that the joint use of these methods could be performed for a better understanding of complex food texture.